Polymorphs, salts, and cocrystals: what's in a name? - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)
The December 2011 release of a draft United States Food and Drug Administration (FDA) guidance concerning regulatory classification of pharmaceutical cocrystals of active pharmaceutical ingredients (APIs) addressed two matters of topical interest to the crystal engineering and pharmaceutical science communities: (1) a proposed definition of cocrystals; (2) a proposed classification of pharmaceutical cocrystals as dissociable ``API-excipient'' molecular complexes. The Indo U.S. Bilateral Meeting sponsored by the Indo-U.S. Science and Technology Forum titled The Evolving Role of Solid State Chemistry in Pharmaceutical Science was held in Manesar near Delhi, India, from February 2-4, 2012. A session of the meeting was devoted to discussion of the FDA guidance draft. The debate generated strong consensus on the need to define cocrystals more broadly and to classify them like salts. It was also concluded that the diversity of API crystal forms makes it difficult to classify solid forms into three categories that are mutually exclusive. This perspective summarizes the discussion in the Indo-U.S. Bilateral Meeting and includes contributions from researchers who were not participants in the meeting.

Polymorphs, salts and cocrystals: what's in a name? (vol 12, pg 2147, 2012) - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)

Porous porphyrin organic polymer for visible light triggered hydrogen production - Mukherjee, Gargi (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Photocatalysis; Porous Porphyrin Organic Polymer (PPOP); titania

Porous porphyrin organic polymer (PPOP) for visible light triggered hydrogen production - Mukherjee, Gargi; Thote, Jayshri; Aiyappa, Harshitha Barike; Kandambeth, Sharath; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
A visible light active porphyrin-based porous organic polymer having high chemical stability and surface area has been synthesized and its ability to influence the photocatalytic activity of large band gap-TiO2 nanoparticles has been tested. The resultant composite shows improved photocatalytic activity as compared to the parent precursors. This study provides insights into the photosensitizing ability of the polymer in addition to its ability to firmly harbor nanoparticles onto its surface.

Polymer nanocomposites with UiO-derived zirconia fillers for energy generation and pressure-sensing devices: the role of crystal structure and surface characteristics - Mukherjee, Gargi; Verma, Ankur; Madhu, Arjun Hari; Prasad, Bhagavatula L. V.; Karumuthil, Subash Cherumannil (ACS Applied Nano Materials, 2024)
Piezoelectric energy harvesting and pressure sensing using polymer nanocomposites have opened up promising avenues in the field of flexible electronics. Herein, the influence of varying crystal structures of zirconia nanoparticles on a piezoelectric energy-generating zirconia-poly(vinylidene difluoride) (PVDF) composite is investigated, and the fabrication of a security alert pavement unit using the material with an optimized composition is demonstrated. More specifically, two metal-organic frameworks, UiO-66 and UiO-67, were employed to synthesize four different types of zirconia nanoparticles with precise control of the monoclinic and tetragonal phases. Polymer nanocomposite with monoclinic zirconia nanoparticles derived from UiO-66 (ZrO2-66m) performed better than other derivatives with 61% enhancement in the beta phase with respect to pure PVDF. It was hypothesized that the stable crystalline structure of the monoclinic phase might act as a better nucleating agent, and among monoclinic derivatives, ZrO2-66m was found to be more hydrophobic, probably enabling a better interaction with PVDF. Subsequently, a prototype device with a PVDF-ZrO2-66m (P/66m) film was made and tested for its energy generation. The maximum output voltage generated by the device under an irregular biomechanical hand tapping force of 8-9 N was 80 V, while the maximum open circuit current was found to be 65 mu A. The prototype displayed a power of 2162.24 mu W at a load resistance of 1 M Omega. A laboratory scale demonstration was executed with the prototype as an energy-generating and security alert pavement unit. A wireless, Bluetooth-based security alert system supported by an Android application was developed and demonstrated as a promising application with the fabricated prototype. The results and demonstrations validate that the PVDF-monoclinic ZrO2 nanoparticle nanocomposites will be an excellent value addition for flexible, durable energy generation and pressure-sensing applications.
Keywords: energy generation and pressure sensing; piezoelectric materials; PVDF/ZrO2 polymernanocomposite; self-powered devices; wearable electronics